2016
DOI: 10.1364/ol.41.003443
|View full text |Cite
|
Sign up to set email alerts
|

Controlling leakage losses in subwavelength grating silicon metamaterial waveguides

Abstract: Subwavelength gratings (SWG) are photonic structures with a period small enough to suppress diffraction, thereby acting as artificial dielectric materials, also called all-dielectric metamaterials. This property has been exploited in many high-performance photonic integrated devices in the silicon-on-insulator (SOI) platform. While SWG waveguides are theoretically lossless, they may exhibit leakage penalty to the substrate due to a combination of reduced modal confinement and finite thickness of the buried oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…For example, in [16] the modes are weakly confined to the point that the Si handle wafer needs to be undercut to prevent leakage. In [17], the authors demonstrated that there is an exponential relation between the Bloch-Floquet mode effective index and leakage losses in SWG waveguides. This relation does not depend of the specific waveguide geometry, but only on the BOX thickness and the mode effective index (the latter determines the modal confinement).…”
Section: Mitigating Substrate Leakage Lossmentioning
confidence: 99%
“…For example, in [16] the modes are weakly confined to the point that the Si handle wafer needs to be undercut to prevent leakage. In [17], the authors demonstrated that there is an exponential relation between the Bloch-Floquet mode effective index and leakage losses in SWG waveguides. This relation does not depend of the specific waveguide geometry, but only on the BOX thickness and the mode effective index (the latter determines the modal confinement).…”
Section: Mitigating Substrate Leakage Lossmentioning
confidence: 99%
“…The SWG waveguide comprises N = 200 periods, with the total grating length of L = 200· = 40 µm. The nominal duty cycle was chosen as DC = l Si / = 50%, as it provides sufficient vertical confinement to mitigate power leakage to the silicon substrate [25]. Another important consideration when choosing this initial set of geometrical parameters was our interest in the jitter influence on a realistic structure related to a practical application, namely an ultra-broadband 2 × 2 MMI coupler, which we recently reported using the same technological platform [13].…”
Section: Introductionmentioning
confidence: 99%
“…5(b), inset] was measured by sweeping the wavelength of a tunable laser while measuring output power with a power meter. From the measured transmittance function the group index difference (∆n g ) is calculated using the procedure described in [32]. A comparison with the FDTD simulation results [ Fig.…”
Section: Resultsmentioning
confidence: 99%